Molecular characterisation of membrane glycoprotein and 5b protein of nephropathogenic infectious bronchitis virus - A. Balasubramaniam; K. Sukumar; P. Suresh; B. Puvarajan (Veterinary World, 2013)
Background: Infectious bronchitis virus (IBV) affects the upper respiratory tract and the reproductive tract, and some strainscan cause nephritis. Large number of serotypes and genotypes of the virus have been identified and for the most part do notcross-protect. Identifying the genotype or serotype of IBV field strains is empirical for selecting an appropriate candidate toserve as vaccine strain for prevention of infectious bronchitis (IB) disease in chickens. The variant strains of IBV could becirculating among chickens in India and recently nephropathogenic IB was reported. Hence, the present work was aimed tocarry out molecular characterization of nephropathogenic IBV isolates obtained from two different geographical locations ofsouth India, involving relatively conserved regions.Materials and Methods: MIBVPCR and NIBVPCR primers were used to amplify partial M and N gene after synthesizingcDNA. Isolates Ind/KA/07/1 and Ind/TN/07/2 were subjected to direct sequencing as these two isolates are two differentgeographical regions and scored better in induction of lesions during pathotyping.Results: Amino acids of membrane glycoprotein varied on five occasions for the isolate Ind/KA/07/1 when aligned with thatof M 41 strain and isolate Ind/TN/07/2. Eight amino acids of both isolates in 5b protein were different from that of M41 strain.Few point mutations, short deletions and insertions were noticed in the amplified genome, based on the membrane proteinnucleotide sequence comparison.Conclusion: Prevalence of IBV strains with few modifications in conserved regions indicated that there was presence ofvariant IBVin south India.